Pengaruh Service Quality Terhadap Customer Satisfaction Di Orion Coffee Padang - Aisyah Vella Rahma; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research was motivated by the discovery of problems related to service quality and customer satisfaction. This research aims to analyze the influence of service quality on customer satisfaction at Orion Coffee Padang. The population in this study were customers who had visited Orion Coffee Padang with a total sample of 204 respondents obtained using a purposive sampling technique. The data collection technique was carried out using a questionnaire which had been tested for validity and reliability using a Likert scale. The independent variable examined in this research is service quality on customer satisfaction using the PLS-SEM analysis technique. The hypothesis result is that service quality influences customer satisfaction and is acceptable. The t statistical value of service quality on customer satisfaction is 24.831 > 1.96 or the p value given is 0.00 < 0.05. The original sample value was 0.856, indicating a positive direction of the relationship between service quality and customer satisfaction. It was concluded that the service quality variable had a positive effect on customer satisfaction.